1995
DOI: 10.1016/0925-5710(95)00350-2
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Despite the advent of novel therapies and improvements in survival, multiple myeloma (MM) remains an incurable disease. Thus, new treatment strategies including immunotherapies are needed for MM patients with stable disease after induction chemotherapy as well as for disease control in patients with advanced disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Moreover, the prominent siRNA signal detected in tumor, the high signals in kidney are consistent with our previous publications that major clearance route of this nanoparticle is kidney [ 51 ]. We also detected some siRNA signal in the liver, lung, and brain, which may be due to lymphoma associated inflammation in central nervous system [ 57 , 58 , 59 , 60 , 61 ] and other organs. Because our previous studies have shown that this delivery system spares health brain [ 45 ], lung [ 50 ], and other organs/tissues, and is not cleared appreciably by a healthy liver [ 51 ], the present results support the observation that this nanomaterial permeates leaky vasculature associated with tumoral and inflammatory microenvironment.…”
Section: Resultsmentioning
confidence: 95%
“…Moreover, the prominent siRNA signal detected in tumor, the high signals in kidney are consistent with our previous publications that major clearance route of this nanoparticle is kidney [ 51 ]. We also detected some siRNA signal in the liver, lung, and brain, which may be due to lymphoma associated inflammation in central nervous system [ 57 , 58 , 59 , 60 , 61 ] and other organs. Because our previous studies have shown that this delivery system spares health brain [ 45 ], lung [ 50 ], and other organs/tissues, and is not cleared appreciably by a healthy liver [ 51 ], the present results support the observation that this nanomaterial permeates leaky vasculature associated with tumoral and inflammatory microenvironment.…”
Section: Resultsmentioning
confidence: 95%
“…The matrix-valued memory kernel δK αβ µ (q, t) can be expressed in terms of an irreducible memory kernel which is more suitable for applying MCT approximations [85,86]. The concept of irreducible memory functions is also present in modified MCT approaches, e.g.…”
Section: Irreducible Memory Kernelmentioning
confidence: 99%
“…Acute, lymphomatous, chronic, and smoldering variants of ATLL have been identified. CNS involvement is more common in the lymphomatous and acute forms [ 2 , 3 ]. Herein, we report a rare case of ATLL that was originally diagnosed as isolated CNS T-cell lymphoma.…”
Section: Introductionmentioning
confidence: 99%